Archaea diversity in the coastal waters of west Peninsular Malaysia / Saw Suet Yit - Saw, Suet Yit (2014)
In this study, we explored the archaea diversity in four locations (Kuala Selangor, Port Klang, Port Dickson, Sungai Muar) along the Straits of Malacca using the cloning method. Four 16S rDNA clone libraries were constructed with archaea specific primers (Arc21F and Arc958R), and in total, 1074 randomly selected clones were screened by PCR-restriction fragment length polymorphism (PCR-RFLP) analysis using three different restriction enzymes (RsaI, CfoI, and DdeI). Majority of the sequences from three clone libraries were affiliated to Euryarchaeota whereas one clone library (Kuala Selangor) was dominated by Thaumarchaeota sequences. Phylogenetic analysis of 16S rDNA sequences showed high archaea diversity with the Shannon index from 2.16 to 3.24. Using the weighted non-normalized principal coordinate analysis, the archaeal communities of the four sites were clearly separated from each other. Via canonical correspondence analysis, the distribution of OTUs could be related to environmental variables especially chlorophyll a concentration.